Study of the factors influencing the survival of COVID-19-infected patients in Győr-Moson-Sopron County - Szentes, Veronika; Szabó, Dániel Róbert; Riegler, Péter; Szakály, Zsolt; Kovács, Norbert (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
This research aims to contribute to a greater understanding of COVID-19 and its effects by assessing the factors influencing the survival of COVID-19-infected patients in the Győr-Moson-Sopron County region. The impact of age, comorbidities, and number of days on a ventilator on the survival of COVID-19-infected patients by gender and regional unit are presented based on anonymized data from the Petz Aladár County Teaching Hospital. Binary logistic regression was used to analyze explanatory variables’ separate and combined effects. This study shows that age was the most critical determinant of the survival of COVID-19-infected patients, with an increase in age correlating to an elevated probability of death. No significant regional or gender differences in recovery or survival rates were found. This paper, which is grounded in the existing research, offers new insights into then progression of COVID-19 throughout its many waves throughout the region, the impact of local socioeconomic development on medical outcomes, and the relevance of specific comorbidities.